Antecedents and Consequences of Psychological Empowerment: A Literature Review - Dewi Gathmyr; Syamsul Hidayat; Suparno Suparno; Puji Wahono; Agung Dharmawan Buchdadi; Hamidah Hamidah; Ratna Tri Hari Safariningsih (Dinasti Publisher, 2024)
This study aims to explore antecedents of psychological empowerment by analyzing the antecedents and consequences. This study employed a literature review approach by searching for references from previous research from Scopus. Several predetermined criteria were applied to create more relevant studies on psychological empowerment. The literature review was conducted through stages based on the criteria used in bibliometrics. The results indicate that the antecedents of psychological empowerment are influenced by several driving factors, such as leader-member exchange, human resource practices (staffing, training, compensation, performance, job design, and participation), transformational leadership, transactional leadership, servant leadership, authentic leadership, empowering leadership, knowledge sharing, perceived supervisory support, perceived organizational support, self-efficacy, emotional intelligence, psychological leadership, high-commitment work system, organizational performance, employee engagement, ethical leadership, and high-performance work system. The consequences of psychological empowerment influence several factors, including strategy commitment, innovative work behavior, creativity, innovation, positive psychological capital, job characteristics, job embeddedness, proactive work behavior, service-oriented organizational citizenship behavior, self-learning, innovative information systems behavior, service quality efficacy, career satisfaction, work engagement, organizational brilliance, work well-being, work intensity, career intention, creative process engagement, and innovative behavior.